2013
DOI: 10.1111/clr.12206
|View full text |Cite
|
Sign up to set email alerts
|

Dental care providers' decision making regarding maintenance of compromised teeth and implant therapy indication: an analysis of gender and enrollment in teaching positions

Abstract: Results suggest that dentists' decision making did not follow the latest external evidence, which might be related to factors as professional expertise and patients' preferences. Considering the difficulties faced by professionals when handling complex cases, there is an urgent need to establish international protocols and guidelines to help the clinician identify this particular treatment option, which corresponds with their internal evidence and is based on good external evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…However, if the tooth is severely diseased, extraction might be considered. Which decision to make – maintenance or extraction – has been shown to greatly vary among dentists .…”
Section: Introductionmentioning
confidence: 99%
“…However, if the tooth is severely diseased, extraction might be considered. Which decision to make – maintenance or extraction – has been shown to greatly vary among dentists .…”
Section: Introductionmentioning
confidence: 99%
“…29 Recently, treatment planning was analyzed in questionnaire studies with dental practitioners. 30,31 Both studies showed that there is a great variance regarding the treatment plan selected by a dentist for a given clinical situation. The suggested approach was affected by confounders, such as profession, age or gender.…”
Section: Discussionmentioning
confidence: 99%
“…Other variables that are believed to impact on dental care providers’ decision making regarding dental implant therapy are professional expertise, enrollment in teaching positions (Junges et al. ) and – last but certainly not least – patients’ preferences (Hof et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…"Sudoku" graphs displaying the percentage of responses 0 (implant prognosis not affected), 1 (implant prognosis affected to the better, or else first option advantageous) or 2 (implant prognosis affected to the worse, or else second option advantageous). (Junges et al 2013) andlast but certainly not leastpatients' preferences (Hof et al 2014).…”
Section: Figmentioning
confidence: 99%